2011
DOI: 10.1037/a0024457
|View full text |Cite
|
Sign up to set email alerts
|

Predeployment, deployment, and postdeployment risk factors for posttraumatic stress symptomatology in female and male OEF/OIF veterans.

Abstract: [Correction Notice: An erratum for this article was reported in Vol 120(4) of Journal of Abnormal Psychology (see record 2011-19996-001). In the article there was an error in the affiliation bylines for Rani Elwy and Susan Eisen. Their affiliations should have been listed as Edith Nourse Rogers Memorial Veterans Hospital and Department of Health Policy and Management, Boston University School of Public Health.] Prior research on risk factors for posttraumatic stress symptomatology (PTSS) in war-exposed Veteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
105
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 66 publications
11
105
2
Order By: Relevance
“…This study underscored the previous research findings related to military life, including significant differences in female sexual harassment, anxiety, and lack of social support in the military, as well as the prevalence of MST (Street, Vogt, & Dutra, 2009;Vogt, Smith, et al, 2011). The findings in this study expressed that MST was a traumatic event and implicated the military culture of female inferiority as the context of the violence.…”
Section: Discussionsupporting
confidence: 61%
“…This study underscored the previous research findings related to military life, including significant differences in female sexual harassment, anxiety, and lack of social support in the military, as well as the prevalence of MST (Street, Vogt, & Dutra, 2009;Vogt, Smith, et al, 2011). The findings in this study expressed that MST was a traumatic event and implicated the military culture of female inferiority as the context of the violence.…”
Section: Discussionsupporting
confidence: 61%
“…Low social support at homecoming, as well as low current social support, are risk factors for veterans (Schnurr et al, 2004). The presence of relationship concerns during deployment is also an additional risk factor (Vogt et al, 2011). Vogt et al (2011) suggested that relationship concerns may influence the risk of PTSD through their influence the perceived threat of combat experiences.…”
Section: Additional Sociodemographic Risk Factorsmentioning
confidence: 99%
“…Vogt et al (2011) suggested that relationship concerns may influence the risk of PTSD through their influence the perceived threat of combat experiences. Furthermore, Vogt et al (2011) found that concerns about family disruptions during deployment are strong predictors of low social support post-deployment.…”
Section: Additional Sociodemographic Risk Factorsmentioning
confidence: 99%
“…For example, childhood trauma exposure (Danielson et al, 2009;Rosen and Martin, 1998) and mental health symptoms before deployment (Jacobson et al, 2008) are associated with alcohol use (Kelley et al, 2013). Whether combat and noncombat-related trauma exposure confers differential risk for mental health disorders, and thus possibly differential risk for self-medication with substances for female versus male veterans, is inconclusive (e.g., Irish et al, 2010;Tanielian and Jaycox, 2008;Vogt et al, 2011). For instance, some researchers have found that combat-related traumatic event exposure has a stronger association with depression (Tanielian and Jaycox, 2008) and PTSD/PTSS (Irish et al, 2010;Luxton et al, 2010;Skopp et al, 2011;Tanielian and Jaycox, 2008) for women than it does for men.…”
Section: Introductionmentioning
confidence: 97%